(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The process of data mining is exploring databases for useful information and extracting it. Analysis how people interact with websites is the main goal of web usage mining, a subfield of data mining. The main, unobtrusive, and objective way to evaluate Web-based training and learning systems, namely how users engage with course materials, is web use mining. Many mining methods were developed with the classroom in mind, and we will showcase and explain them all. In order to prove effectiveness and improve instructional design as required, it is crucial to analyse and evaluate how learners behave in learning and training technology systems. This is particularly true when there are several interactive learning and training components accessible. We take a look at methods for figuring out what we want to learn, how we’re going to learn it, and how our habits change as we go.